Characteristics of compacted fly ash bricks and fly ash brick masonry - Gourav, K.; Reddy, B. V. Venkatarama (Journal of Structural Engineering, 2024)
Fly ash is used for the manufacture of masonry units such as fly ash bricks and concrete blocks. This paper deals with results of an experimental investigation on the characteristics of fly ash-lime-gypsum bricks and their masonry. Review on the existing literature on fly ash bricks/blocks is presented. Characteristics (strength, absorption and durability) of compacted fly ash – lime bricks with and without gypsum additive were examined. Compressive strength, flexure bond strength and stress strain characteristics of fly ash brick masonry using four types of fly ash bricks and cement-lime mortar were investigated. The results reveal that (1) it is possible to achieve 8 – 10 MPa compressive strength in saturated state, reasonably low values of water absorption, good dimensional stability and durability characteristics for fly ash lime gypsum bricks using 10% lime and 2% gypsum, (2) fly ash bricks of higher density can be produced using fly ash-sand mixture, instead of fly ash alone and (3) fly ash brick masonry shows higher flexure bond strength when compared with that of burnt clay brick masonry.